(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
Starting from The Book of Common Prayer, a text widely used in the seventeenth century, this paper provides the historical and theological context which includes the debate on Mass as performance, that is both as ‘representation’ of the Christ’s sacrifice and as a setting for an event – the ‘transformation’ of the bread and wine into the Christ’s body and blood through the words of consecration pronounced by the priest. It also analyses some figures related to the liturgical aspects of the Eucharist and the poetic attempt to stage a performance of seduction by means of them.